Cobalt-nitrogen doped 3D porous carbon prepared with self-generated nanoparticles as sacrificial templates for hydrogen generation. (16th February 2017) - Zhang, Zhengping; Yang, Shaoxuan; Dou, Meiling; Ji, Jing; Wang, Feng
Abstract: To obtain clean and sustainable alternative energy, the development of low-cost, high efficient, wide pH range and durable non-precious metal electrocatalysts for hydrogen evolution reaction (HER) has become one of the crucial issues for the large-scale application of water splitting. We demonstrate a simple and efficient synthetic strategy for the preparation of cobalt-nitrogen codoped hierarchically porous carbon (Co-NHPC) electrocatalysts towards HER, by the direct carbonization followed by removing the Co nanoparticles. The resultant carbon-based materials were demonstrated to be three-dimensional porous graphitic structure with the highly active Co–N–C complex, leading to a high electrocatalytic activity and durability for HER in both of alkaline and acidic electrolyte. Considering the facial and rational preparation processes, the self-sacrificial nanoparticle templates synthetic strategy developed in this work is promising to design other carbon-based materials for other electrochemical applications. Graphical abstract: Abstract : Carbon materials as the excellent HER catalysts over wide pH range. Co-NHPC by a sacrificial self-generated cobalt nanoparticle template synthesis. Layered texture with inter-lamellar spacing and mesoporous structure. Higher activity of Co–N–C complex than Co nanoparticle.